Escleritis necrotizante como presentación ocular de la granulomatosis de Wegener - Larcos Andrade, Mónica Gabriela (2016)
Wegener’s granulomatosis (WG) is a systemic small vessel vasculitis with autoimmune etiology, and it is characterized by the formation of granulomas in small and medium vessels, mainly involving the respiratory system and kidneys. It shows a case report of a 78-year-old male patient who reported the onset of the disease in October 2013, with palpebral edema of the right eye followed by exophthalmos and impossibility of lid closure, accompanied by a significant decrease in visual acuity. Intermittent fever of 38 degrees Celsius, cyanotizing dr cough with episodes of dyspnea. After his admission to the Carlos Andrade Marín Hospital, imaging studies revealed a right orbital mass undergoing resection. Histopathology confirms the diagnosis of Wegener’s granulomatosis. He received treatment with steroids and cycl phosphamide, achieving normalization of renal function and full resolution of the ocular symptom.